Mothers’ Knowledge of and Practices Toward Oral Hygiene of Children Aged 5-9 Years in Bangladesh: Cross-Sectional Study - Tahazid Tamannur; Sadhan Kumar Das; Arifatun Nesa; Foijun Nahar; Nadia Nowshin; Tasnim Haque Binty; Shafiul Azam Shakil; Shuvojit Kumar Kundu; Md Abu Bakkar Siddik; Shafkat Mahmud Rafsun; Umme Habiba; Zaki Farhana; et al. (JMIRx Med)
Abstract BackgroundHealthy oral hygiene is crucial for overall health and well-being. Parents’ dental care knowledge and practices affect their children’s oral health. ObjectiveThis study examined mothers’ knowledge and practices regarding their children’s oral hygiene through a cross-sectional survey. MethodsThis cross-sectional survey was conducted from January 1 to December 31, 2022, in Dhaka, Bangladesh. Mothers’ knowledge and practices regarding their children’s oral hygiene were assessed through a semistructured questionnaire. Statistical analyses, including the χ2U ResultsOf 400 participants, the mean age of mothers was 30.94 (SD 5.15) years, and 388 (97%) were of the Muslim faith, 347 (86.8%) were housewives, and 272 (68%) came from nuclear families. A total of 165 (41.3%) participants showed good knowledge of their children’s oral hygiene, followed by 86 (21.5%) showing moderately average knowledge, 75 (18.8%) showing average knowledge, and 74 (18.5%) showing poor knowledge. A total of 182 (45.5%) mothers had children with good oral hygiene practices, followed by mothers with children who had average (n=78, 19.5%), moderately average (n=75, 18.8%), and poor (n=65, 16.3%) oral hygiene practices. The mother’s knowledge level was significantly associated with age (PPPPPPPPPPPPrPχ2P ConclusionsThe mothers’ knowledge and their children’s oral hygiene practices were inadequate. The mother’s age, education level, family size, and monthly income significantly influenced their knowledge level. Children’s oral hygiene habits were significantly associated with family income and the mother’s educational status. This underscores the need for educational programs, accessible dental care services, oral health education in the curriculum, media and technology involvement in oral health educational campaigns, and proper research and monitoring.